The Influence of Youtube Media on Writing Short Story Texts in Class VI Students of SD Negeri 2 Percontohan Blangkejeren - Fitria Ratnawati; Sadieli Telaumbanua; Yenita Br. Sembiring (Universitas Negeri Semarang, 2024)
The research entitled